Retinal Pigment Epithelium Rips After Ranibizumab in Neovascular Age-Related Macular Degeneration: Incidence, Risk Factors and Long-Term Outcome - Guber, J.; Praveen, A.; Saeed, M. U. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: Retinal pigment epithelium (RPE) rips after ranibizumab for wet age related macular degeneration (AMD) with a pigment epithelial detachments (PED) are a dreaded complication. Aim of this study was to analyse the incidence, the risk factors and long-term outcome after a PED tear. Patients and Methods: 401 patients with wet AMD were analysed. A total of 33 eyes with PED were identified. Mean follow up time was 635 days (SD ± 311). Results: PED tears occurred in 8 (24 %) patients. Most RPE rips (40 %) occurred within the first three months. Mean visual loss was 13 letters (range − 57–9). The PED tear group had a mean PED height of 521 µm. The PED group without a tear had a mean height of 300 µm (p ≤ 0.001). Patients with a PED height over 300 µm had more than twice the risk to develop a RPE rip compared to patients with PED height smaller than 300 µm (p ≤ 0.001). Conclusions: PED height is a relevant factor for the incidence of RPE rips after treatment with ranibizumab. Owing to the close time relationship with the therapy, this complication must be taken into account before treatment as it may lead to significant vision loss.
Keywords: age-related macular degeneration; retinal pigment epithelium rip; ranibizumab